Implementasi Kebijakan Tentang Rencana Tata Ruang Wilayah Dalam Pengembangan Kawasan Agropolitan (Studi pada Kawasan Agropolitan Kecamatan Nganjuk dan Kecamatan Sukomoro di Kabupaten Nganjuk) - Alday Julian Pradana (Jurnal Administrasi Publik, 2016)
Abstract: Policy Implementation of Spatial Region’s Plans on Regional  Agropolitan  Development (Studies on Agropolitan Area Kecamatan Nganjuk and Kecamatan Sukomoro in Kabupaten Nganjuk). Kabupaten Nganjuk as one that has great potential in the agricultural sector, developing concept of agropolitan as one way for the welfare of the people in Kabupaten Nganjuk. Regional agropolitan development in Nganjuk was started in 2009. So far the implementation of regional  agropolitan  developmenting Nganjuk generally have been going well despite that still appear some issues, such as communication and coordination between implementer of regional  agropolitan  developmenting Nganjuk, capitalization problem, marketing of agricultural products, and overlap between the Spatial Region’s Plans Nganjuk and the establishment of regional agropolitan  developmentin Nganjuk. Nganjuk government is expected to provide access to capitalization by giving incentives to farmers and by cooperating with government banks to provide soft loans. For problem of overlapping policies of regional  agropolitan  development should be the Kecamatan Nganjuk that as urban areas replace by other Kecamatan as the rural areas but also meet the requirements of regional agropolitan  development so that kecamatan are totally focused on development of agropolitan.   keywords: policy implementation, spatial region’s plans, regional  agropolitan  development Abstrak: Implementasi Kebijakan Tentang Rencana Tata Ruang Wilayah Dalam Pengembangan Kawasan Agropolitan (Studi pada Kawasan Agropolitan Kecamatan Nganjuk dan Kecamatan Sukomoro di Kabupaten Nganjuk). Kabupaten Nganjuk sebagai salah satu Kabupaten yang memiliki potensi besar di sektor pertanian, mengembangkan konsep agropolitan sebagai salah satu cara untuk mensejahterakan masyarakat di kabupaten Nganjuk. Pengembangan kawasan agropolitan di Kabupaten Nganjuk mulai dilaksanakan efektif pada tahun 2009. Sejauh ini implementasi pengembangan kawasan agropolitan di Kabupaten Nganjuk pada umumnya sudah berjalan dengan baik meskipun begitu masih muncul beberapa masalah, seperti masalah komunikasi dan koordinasi antar pelaksana pengembangan kawasan agropolitan di Kabupaten Nganjuk, masalah permodalan, pemasaran hasil pertanian, dan adanya tumpang tindih kebijakan antara RTRW Kabupaten Nganjuk dan penetapan kawasan pengembangan agropolitan di Kabupaten Nganjuk. Pemerintah Kabupaten Nganjuk diharapkan mampu memberikan akses permodalan dengan memberikan insentif kepada petani dan dengan menggandeng bank pemerintah untuk memberikan kredit lunak. Untuk masalah tumpang tindihnya kebijakan tentang penetapan kawasan agropolitan sebaiknya Kecamatan Nganjuk yang sebagai kawasan perkotaan digantikan kecamatan lain yang merupakan kawasan perdesaan tetapi juga memenuhi syarat-syarat dalam pengembangan kawasan agropolitan sehingga kecamatan tersebut benar-benar fokus dalam pengembangan kawasan agropolitan.   Kata kunci: implementasi kebijakan, rencana tata ruang wilayah, pengembangan kawasan agropolitan